Girl Scouts of Colorado - Front Range Fuels Treatment Partnership - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2008)
Located in: Fort Collins office files. Girl Scouts of Colorado records related Colorado State Forest Service (CSFS) Front Range Fuels Treatment Partnership (FRFTP) program for Magic Sky Ranch Fuels Reduction Project. Includes: Wildland Urban Interface (WUI) grant application; program payment and reimbursement requests; accomplishment report; invoices; re-encumbrance statement; request for supplies or services; application for cost-share; correspondence to include printed email; and maps.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado